The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1103/physreva.94.053632
|View full text |Cite
|
Sign up to set email alerts
|

Ultraquantum turbulence in a quenched homogeneous Bose gas

Abstract: Using the classical field method, we study numerically the characteristics and decay of the turbulent tangle of superfluid vortices which is created in the evolution of a Bose gas from highly nonequilibrium initial conditions. By analysing the vortex line density, the energy spectrum and the velocity correlation function, we determine that the turbulence resulting from this effective thermal quench lacks the coherent structures and the Kolmogorov scaling; these properties are typical of both ordinary classical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…A recent work [54] has examined the properties of the turbulence following a thermal quench of a Bose gas. It found that topological defects created by the Kibble-Zurek mechanism evolve into a turbulent vortex tangle [68] which eventually decays into a vortex free state.…”
Section: Identification Of the Turbulencementioning
confidence: 99%
“…A recent work [54] has examined the properties of the turbulence following a thermal quench of a Bose gas. It found that topological defects created by the Kibble-Zurek mechanism evolve into a turbulent vortex tangle [68] which eventually decays into a vortex free state.…”
Section: Identification Of the Turbulencementioning
confidence: 99%
“…Physically, ultraquantum turbulence is a state of disorder without an energy cascade 42 . Recently, it has been argued that ultraquantum turbulence has also been observed in the thermal quench of a Bose gas 43 , and in small trapped atomic condensates 44 .…”
Section: Total Reflection From the Unstructured Vortex Tanglementioning
confidence: 99%
“…A typical scale used to study turbulence in liquid helium is the vortex line density. Its time dependence provides evidence of the mechanism behind the turbulent regime [13]. In some 4 He experiments, where visualization techniques are well-developed, the geometry and interactions of vortices can be directly observed [14].…”
Section: Introductionmentioning
confidence: 99%
“…It is inspired by the integral length scale, which is a quantity commonly used in classical turbulence. If we assume isotropic flow, then the integral length scale L E can be written in terms of the incompressible kinetic energy spectrum E(k) [13,15,16],…”
Section: Introductionmentioning
confidence: 99%